A prospective, multicenter analysis of the integrated 31-gene expression profile test for sentinel lymph node biopsy (i31-GEP for SLNB) test demonstrates reduced number of unnecessary SLNBs in patients with cutaneous melanoma - J. Michael Guenther; Andrew Ward; Brian J. Martin; Mark Cripe; Rohit Sharma; Stanley P. Leong; Joseph I. Clark; John Hamner; Timothy Beard (World Journal of Surgical Oncology)
Abstract Background National Comprehensive Cancer Network guidelines recommend sentinel lymph node biopsy (SLNB) for patients with > 10% risk of positivity, consider SLNB with 5–10% risk, and foregoing with < 5% risk. The integrated 31-gene expression profile (i31-GEP) algorithm combines the 31-GEP with clinicopathologic variables, estimating SLN positivity risk. Methods The i31-GEP SLNB risk prediction accuracy was assessed in patients with T1-T2 tumors enrolled in the prospective, multicenter DECIDE study (n = 322). To determine if incorporating the i31-GEP into decision-making resulted in fewer SLNBs performed, propensity score-matching was performed to a non-overlapping cohort for whom the 31-GEP was not used for SLNB decision-making. Results No patients with < 5% i31-GEP predicted risk had a positive SLNB (0/35). Propensity matching demonstrated an 18.5% reduction in SLNBs performed (43.7% vs. 62.2%. p < 0.001). The i31-GEP could have reduced the number of unnecessary biopsies by 25.0% (35/140). Conclusions This prospective study confirmed the performance and clinical utility of the i31-GEP for SLNB for improving risk-aligned care and demonstrated a significantly reduced SLNB performance rate when incorporating the i31-GEP into clinical decision-making.